JAM'UL QUR'AN MASA NABI MUHAMMAD SAW - Irpina Irpina; Istiqamah; Nuril Anisa (CV. Adiba Aisha Amira, 2022)
The Qur'an is the word of God which is full of miracles, and will always be in accordance with the development of the times and times. Muslims should use the Al-Quran as a solution to every problem they face because the development of the Ulum Al-Qur'an era has a very broad discussion so that it seems complicated to understand and the dominant Arabic language is also the reason most people in Indonesia find it difficult to learn it. Rasulullah SAW was the first person to memorize the Quran. Some of the Companions also wrote the Koran on their own initiative on palm fronds, stone slabs, thin boards, leather or wood leaves, saddles, and pieces of animal bones. the factor that prompted the codification was the large number of qurra who were killed on the battlefield so it was feared that this would continue to happen and have an impact on the extinction of the huffazh companions and lead to the extinction of the Koran itself.